Compromised Dynamic Cerebral Autoregulation in Patients With Central Disorders of Hypersomnolence - Deng, Fang; Zhang, Yanan; Zhang, Ran; Tang, Qi; Guo, Zhenni; Lv, Yudan; Wang, Zan; Yang, Yi (Frontiers in Neurology, 2021)
Objective: We aimed to investigate the dynamic cerebral autoregulation (dCA) in patients with central disorders of hypersomnolence during wakefulness. Methods: Thirty-six patients with central disorders of hypersomnolence were divided into three groups according to polysomnography and multiple sleep latency test results: the idiopathic hypersomnia group (IH), narcolepsy type 1 without rapid-eye-movement sleep behavior disorder group (NT1-RBD), and narcolepsy type 1 with rapid-eye-movement sleep behavior disorder group (NT1 + RBD), with 12 patients in each group. Twelve sex- and age-matched healthy controls were recruited. We assessed the Epworth sleepiness scale (ESS) and dCA of all subjects. dCA was assessed by analyzing the phase difference (PD) using transfer function analysis. The ESS and dCA were analyzed before and after standardized treatment in 24 patients with narcolepsy type 1. Results: The overall PD of the IH, NT1-RBD, and NT1 + RBD groups were lower than that of the control group (P < 0.001). There were no significant differences between the overall PD of the NT1-RBD and NT1 + RBD group (P > 0.05). The ESS scores decreased and the overall PD increased after treatment in 24 patients with narcolepsy type 1 (P < 0.001). Multivariable analysis showed that mean sleep latency in multiple sleep latency test was independently associated with impaired overall PD (P < 0.05). Conclusions: The dCA is impaired in patients with central disorders of hypersomnolence. The impairment of dCA occurs irrespective of NT1-RBD/+RBD. The ESS score and dCA improved in patients with narcolepsy type 1 after medication treatment. The mean sleep latency in multiple sleep latency test was independently associated with impaired dCA. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT02752139.